Comparison of physical and chemical method for removing copper from non-metallic printed circuit board scrap - Nor Yuliana Yuhana,; Nur Hidayatul Nazirah Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Printed circuit boards (PCBs) are the basic components of electrical and electronic devices. E-waste management is challenging to implement due to accompanying difficulties and danger. Valuable metals and copper (Cu) are primarily recycled through various methods in the treatment of waste PCB. A large number of non-metals materials in PCBs are disposed of through combustion or in landfill, resulting in secondary pollution and resource waste. To reduce the amount of waste non-metallic PCB (NMPCB) and the influences toward environment, recent studies focused on the usage of NMPCB as filler to replace raw material. NMPCB as filler seems to have a good interaction with the raw materials and thus can enhance the strength of the newly formed product. In our study, we focused on developing new NMPCB added with waste NMPCB. Commercial NMPCBs are often a flat laminated composite comprising non-conductive substrate materials. Hence, pre-treatment methods to remove metals, especially Cu, must be investigated. The present study attempted to remove the Cu layer on PCB by using chemical and physical methods. The untreated and Cu removed PCB residues were characterized using X-ray diffraction (XRD), scanning electron microscopy, and infrared spectroscopy (FTIR) for the determination of structural and functional groups and hydrophobicity test. XRD analysis indicated that the Cu in untreated PCB was successfully removed using physical and chemical methods.